Yarning as decolonial praxis in initial teacher training: an Australian context - Fricker, Aleryk (Frontiers in Sociology, 2025)
Yarning has been a widespread practice for First Nations people across the Australian continent for approximately 70,000 years. Yarning as a process of communication has been designed to support authentic and relational connections between people, Country, ancestors, spirits, and the more-than-human realms. In recent scholarship, the process of yarning has emerged in a western context as being a legitimate research method for gathering rich qualitative data. It has also been found to be able to support social connections, collaborations, and processing and sharing trauma. This paper explores collaborative yarning as a pedagogical process in initial teacher training in Australia through auto-ethnographic reflections, and how engaging with yarning as a pedagogical process can challenge the neo-colonial pedagogies that have dominated higher education in Australia for over a century. This paper has found that when engaging with yarning in Higher Education, it can provide an important opportunity to reduce the neo-colonial violence present.